Uvarinol and Dichamanetin Derived from Uvaria chamae as Potential Dual-Site Inhibitors Against PBP2a in Methicillin Resistant Staphylococcus aureus: An In Silico Study - Emmanuel Ayodeji Agbebi; Shalom Oluwafunke Adeyemi; Adetola Ibukunoluwa Adewale; Omolara Seun Ajofoyinbo; Ezekiel Abiola Olugbogi; Oluwatoyin Mary Oyinloye; Iyadunni Adesola Anuoluwa; Timothy Oluwaseyi Agbebi; Basiru Olaitan Ajiboye; Babatunji Emmanuel Oyinloye (Pharmaceuticals)
Background/Objectives: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the resistant pathogenic microorganisms that poses a global health threat due to its resistance to β-lactam antibiotics where the protein penicillin-binding protein 2a (PBP2a) plays a crucial role in its resistance. This study explores the potential of phytochemicals from Uvaria chamae, a plant with known medicinal properties, to serve as dual-site inhibitors of PBP2a, targeting both the active and allosteric sites. Methods: Phytochemicals previously identified in U. chamae were subjected to molecular docking and molecular dynamics simulations to evaluate their binding affinities and stability at PBP2a’s active and allosteric sites. The compounds’ pharmacokinetic profiles were predicted in silico using SwissADME tools. Root-mean-square deviation (RMSD), radius of gyration, and binding free energy were analyzed for dynamic stability. Results: Among the evaluated compounds, Uvarinol and Dichamanetin demonstrated high binding affinities compared to the co-crystallized ligand and standard antibiotics like ceftaroline. Uvarinol exhibited the highest binding affinity at both sites, with a docking score of −14.94 kcal/mol and a predicted inhibition constant (Ki) of 0.01 nM. Molecular dynamics simulations further confirmed the robust stability of Uvarinol and Dichamanetin, as indicated by consistently lower RMSD values relative to the co-crystallized ligand. Pharmacokinetic predictions revealed favorable drug-likeness and low toxicity, although Uvarinol showed limited gastrointestinal absorption. Conclusions: Uvarinol and Dichamanetin show promise as dual-site PBP2a inhibitors, offering a novel strategy to combat MRSA resistance. Their structural and pharmacokinetic properties make them viable candidates for further development, though experimental validation and formulation optimization are necessary to overcome bioavailability challenges.